Intervensi Kebijakan Pusat dan Efisiensi Alokasi Dana Desa: Analisis Kebijakan dalam Perspektif Akuntansi Sektor Publik - Zulkan (Cendekia Inovatif Dan Berbudaya, 2026)
Village Fund management faces the challenge of balancing central government policy direction with the need to preserve village governments’ fiscal discretion. This study aims to analyze the implications of central government policy intervention for fiscal space, administrative burden, and the allocation efficiency of Village Funds from a public sector accounting perspective. The study employs a qualitative approach using policy and document analysis of Village Fund regulations, particularly Minister of Finance Regulation (PMK) No. 108 of 2024, PMK No. 81 of 2025, and PMK No. 7 of 2026, as well as relevant official documents and government publications. The analysis was conducted through identification, classification, interpretation, and synthesis, using Agency Theory and the Value for Money concept as analytical perspectives. The findings indicate that the development of Village Fund regulations reflects an increasing specification of central government direction through designated uses, disbursement requirements, and allocation adjustments, which may potentially narrow village fiscal discretion. Regulatory dynamics may also increase the administrative adjustment burden, while compliance pressures and implementation deadlines may create a risk of shifting the focus from development outcomes toward procedural compliance. This study argues that the effectiveness of Village Fund governance is determined not only by regulatory compliance but also by the capacity of policy design to balance central control, local flexibility, administrative capacity, and the achievement of economy, efficiency, and effectiveness in the use of public resources.